Cardiovascular Safety in Drug Development and Therapeutic Use : New Methodologies and Evolving Regulatory Landscapes /: New Methodologies and Evolving Regulatory Landscapes. (2017) - Turner, J. Rick; Karnad, Dilip R; Kothari, Snehal
No abstract available